Impact of polyvascular disease on patients with atrial fibrillation: insights from ROCKET AF - Chen, Sean T.; Hacke, Werner (American heart journal, 2018)
Background: We investigated the impact of polyvascular disease in patients enrolled in ROCKET AF. Methods: Cox regression models were used to assess clinical outcomes and treatment effects of rivaroxaban compared with warfarin in patients with atrial fibrillation and coronary, peripheral, or carotid artery disease, or any combination of the 3. Results: A total of 655 (4.6%) patients had polyvascular disease (≥2 disease locations), and 3,391 (23.8%) had single-arterial bed disease. Patients with polyvascular disease had similar rates of stroke/systemic embolism but higher rates of cardiovascular and bleeding events when compared with those without vascular disease. Use of rivaroxaban compared with warfarin was associated with higher rates of stroke in patients with polyvascular disease (hazard ratio [HR] 2.41, 95% CI 1.05-5.54); however, this was not seen in patients with single-bed (HR 0.90, 95% CI 0.64-1.28) or no vascular disease (HR 0.85, 95% CI 0.69-1.04; interaction P = .058). There was a significant interaction for major or nonmajor clinically relevant bleeding in patients with polyvascular (HR 1.23, 95% CI 0.91-1.65) and single-bed vascular disease (HR 1.30, 95% CI 1.13-1.49) treated with rivaroxaban compared with warfarin when compared with those without vascular disease (HR 0.95, 95% CI 0.87-1.04; interaction P = .0006). Additional antiplatelet therapy in this population did not improve stroke or cardiovascular outcomes. Conclusion: The use of rivaroxaban compared with warfarin was associated with a higher risk of stroke and bleeding in patients with polyvascular disease enrolled in ROCKET AF. Further studies are needed to understand the optimal management of this high-risk population.